Mini-Me: A Min-Repro System for Database Systems - Bruno, Nicolas; Nehme, Rimma (ICDE, 2010)
Testing and debugging database software is often challenging and time consuming. A very arduous task for DB testers is finding a min-repro – the “simplest possible setup” that reproduces the original problem. Currently, a great deal of searching for min-repros is carried out manually using nondatabase-specific tools, which is both slow and error-prone. We propose to demonstrate a system, called Mini-Me1, designed to ease and speed-up the task of finding min-repros in databaserelated products. Mini-Me employs several effective tools, including: the novel simplification transformations, the high-level language for creating search scripts and automation, the “record-and-replay” functionality, and the visualization of the search space and results. In addition to the standard application mode, the system can be interacted with in the game mode. The latter can provide an intrinsically motivating environment for developing successful search strategies by DB testers, which can be datamined and recorded as patterns and used as recommendations for DB testers in the future. Potentially, a system like Mini-Me can save hours of time (for both customers and testers to isolate a problem), which could result in faster fixes and large cost savings to organizations.